Effect of urbanization on soil methane and nitrous oxide fluxes in subtropical Australia. (7th October 2018) - van Delden, Lona; Rowlings, David W.; Scheer, Clemens; De Rosa, Daniele; Grace, Peter R.
Abstract: Increasing population densities and urban sprawl are causing rapid land use change from natural and agricultural ecosystems into smaller, urban residential properties. However, there is still great uncertainty about the effect that urbanization will have on biogeochemical C and N cycles and associated greenhouse gas (GHG) budgets. We aimed to evaluate how typical urbanization related land use change in subtropical Australia affects soil GHG exchange (N2 O and CH4 ) and the associated global warming potential (GWP). Fluxes were measured from three land uses: native forest, a long‐term pasture, and a turf grass lawn continuously over two years using a high‐resolution automated chamber system. The fertilized turf grass had the highest N2 O emissions, dominated by high fluxes >100 g N2 O‐N day −1 immediately following establishment though decreased to just 0.6 kg N2 O‐N ha −1 in the second year. Only minor fluxes occurred in the forest and pasture, with the high aeration of the sandy topsoil limiting N2 O emissions while promoting substantial CH4 uptake. Native forest was consistently the strongest CH4 sink (−2.9 kg CH4 ‐C ha −1 year −1 ), while the pasture became a short‐term CH4 source after heavy rainfall when the soil reached saturation. On a two‐year average, land use change from native forest to turf grass increased the non‐CO2 GWP from a net annual GHG sink of −83 CO2 ‐e ha –1 year −1 to a source of 245 kg CO2 ‐e ha –1 year −1 . This study highlights that urbanization can substantially alter soil GHG exchange by altering plant soil water use and by increasing bulk density and inorganic N availability. However, on well‐drained subtropical soils, the impact of urbanization on inter‐annual non‐CO2 GWP of turf grass was low compared to urbanized ecosystems in temperate climates. Abstract : Increasing population and urban sprawl are causing rapid land use change, and the effect this has on soil nutrient cycles and greenhouse gas budgets is unclear. Fluxes of N2 O and CH4 were measured from native forest, pasture and turf grass continuously over two years using an automated chamber system. The fertilized turf increased N2 O emissions immediately following establishment, though all land uses were a net sink for CH4 . Land use change from native forest to turf grass increased non‐CO2 GWP from a net annual GHG sink of −83 CO2 ‐e ha −1 year −1 to a source of 245 kg CO2 ‐e ha −1 year −1 .